Analisa Potensi Wisata Kuliner dalam Mempertahankan Kearifan Lokal Kuliner Tradisional di Pasar Kanoman Kota Cirebon - Ety Setiawati; Khairil Sungkawa (STIKes Ibnu Sina Ajibarang, 2024)
The attraction of Kanoman Market can be seen from the variety of products sold, including traditional culinary products. Based on the researcher's observations, furthermore, the Kanoman Market is not just a place to buy and sell. Kanoman Market is a conception of life and socio-cultural interaction, as well as a means of recreation or culinary tourism in Cirebon City. The Kanoman market and the traditional culinary sold in this market, is a culture that must be maintained and maintained, because it is part of the local wisdom of Cirebon City. The analysis method used in this study is a descriptive analysis method, using primary data and secondary data. To obtain primary data, interview techniques were used by distributing questionnaires and using a checklist of potential research objects. Secondary data was obtained by conducting a literature study and data from the manager of the Kanoman Market. The expected result of the research is the discovery of the potential of Kanoman Market as a culinary tourism destination. The aspects analyzed are the diversity of traditional culinary, authenticity, local wisdom, completeness and feasibility of supporting facilities owned by Kanoman Market as a culinary tourist attraction. With the known potential of culinary tourism in Kanoman Market, efforts can be made to maintain and improve local wisdom. The level of technological readiness (TKT) of this study is the basic research of TKT level 3.